Combining SMED methodology and ergonomics for reduction of setup in a turning production area - Brito, A. M. (2017)
The aim of this study is to prove that it is possible to reduce the setup time and improve ergonomic conditions at the same time. This research took place in a turning production area of a metallurgical factory where workers’ complains due to shoulder pains and tendinitis were high, due to the awkward postures and forceful hand exertions to perform the manual tasks. Moreover, the high setup time of 105 minutes caused productivity problems and delays for customers. Through the SMED tool and increasing ergonomic conditions, the setup time was reduced 46% and the MSD risk also decreased.